Prototypical and non-prototypical reading of a poetic text (a case study of American poetry) - Belekhova, L. I. (Cognition, Communication, Discourse, 2018)
This article aims to elicit cognitive processes and operations which underpin prototypical and non-prototypical readings of a poetic text. Prototypical reading is the central reading of a poetic text, the one which provides an access to the content and message of the text, as seen by most interpreters. A non-prototypical reading of a poetic text results in its multiple interpretations, leading either to in-depth interpretation, which captures some marginal hidden senses of the text, or to under-interpretation that ignores the subtle nuances of semantics, inherent in a verbal poetic image integrated into the imagery space of a poetic text.